Actin mesh in Re-epithelialization during skin regeneration in adult newt (Cynops pyrrhogaster) - Yu Liou; Nobuko Moritoki; Tomoko Shindo; Tatsuyuki Ishii; Kazuo Kishi (Regenerative Therapy)
Introduction: Studies have highlighted the role of actin cables in embryonic scarless wound healing across various species. However, evidence for similar structures in adult animals remains lacking. Adult newts, known for their exceptional skin regeneration capabilities, are considered promising models for postnatal human studies. This study investigated actin fiber formation and alignment during re-epithelialization in the Japanese fire-bellied newt (Cynops pyrrhogaster). Methods: Full-thickness skin excisions were performed, and actin structures were analyzed using immunohistochemistry and electron microscopy. The role of actin in re-epithelialization was assessed by inhibiting its formation with cytochalasin B. Myosin, an interacting cytoskeletal molecule, was examined through immunohistochemistry, while E-cadherin, an adhesion molecule, was analyzed using both immunohistochemistry and electron microscopy. Results: Rather than an actin cable a mesh-like actin structure, termed the “actin mesh,” was identified via immunohistochemical analysis. The actin mesh developed alongside wound epidermis extension and disappeared following complete re-epithelialization. Inhibition of actin formation delayed re-epithelialization, although the overall healing process showed no significant difference from the control group. Immunohistochemistry revealed the presence of myosin II and E-cadherin alongside Filamentous actin. Electron microscopy further demonstrated actin-rich structures in the wound epidermis compared to normal skin and confirmed E-cadherin-mediated cell-cell adhesion in the wound area. Conclusions: The actin mesh plays a critical role in facilitating rapid re-epithelialization in adult newts, presenting a valuable model for studying scarless wound healing in adult organisms. The involvement of interacting molecules such as myosin and E-cadherin provides insights into the underlying mechanisms of this process. This model offers potential applications for addressing intractable wounds in humans.